The Students' Perception of The Media Used by Teacher In Teaching English - Hadiwijaya, Rangga (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
The Students'Perception of the Media Used by Teacher in Teaching English (A Descriptive Research at the tenth Grade Students of SMK 1 Tirtamulya Karawang) under the thesis of English Education Department the Faculty of Teacher Training and Education, University of Singaperbangsa Karawang, guided by Fauzi Miftakh and Tika Santika. This research aimed to find out (1) the kinds of media used by the teacher in teaching English; (2) The Students Perception of the media used by the teacher in teaching English. The data were conducted on October 2021 from 10 students of the tenth Grade Students at SMK 1 Tirtamulya Karawang from two Classes. This used a Descriptive qualitative research; the instrument were an observation and interview.